Towards standardization of the parameters for opening the blood–brain barrier with focused ultrasound to treat glioblastoma multiforme: A systematic review of the devices, animal models, and therapeutic compounds used in rodent tumor models - Thombre, Rasika; Mess, Griffin; Kempski Leadingham, Kelley M.; Kapoor, Shivani; Hersh, Andrew; Acord, Molly; Kaovasia, Tarana; Theodore, Nicholas; Tyler, Betty; Manbachi, Amir (Frontiers in Oncology, 2023)
Glioblastoma multiforme (GBM) is a deadly and aggressive malignant brain cancer that is highly resistant to treatments. A particular challenge of treatment is caused by the blood–brain barrier (BBB), the relatively impermeable vasculature of the brain. The BBB prevents large molecules from entering the brain parenchyma. This protective characteristic of the BBB, however, also limits the delivery of therapeutic drugs for the treatment of brain tumors. To address this limitation, focused ultrasound (FUS) has been safely utilized to create transient openings in the BBB, allowing various high molecular weight drugs access to the brain. We performed a systematic review summarizing current research on treatment of GBMs using FUS-mediated BBB openings in in vivo mouse and rat models. The studies gathered here highlight how the treatment paradigm can allow for increased brain and tumor perfusion of drugs including chemotherapeutics, immunotherapeutics, gene therapeutics, nanoparticles, and more. Given the promising results detailed here, the aim of this review is to detail the commonly used parameters for FUS to open the BBB in rodent GBM models.